Effects of coating precursor states on performance of titanium-based metal oxide coating anode for Mn electrowinning. (20th December 2021) - Xie, Xionghui; Chang, Linhui; Chen, Buming; Li, Jiamin; Huang, Hui; Guo, Zhongcheng; He, Yapeng
Abstract: In this paper, the effects of different coating precursor states and concentrations on the properties of titanium-based metal oxide coatings were investigated. The excess water in the precursor were removed by two methods. The molar ratio of Sn:Sb:Ru:Co in the precursor was 6:1:1:0.8; 0.006–0.024 mol Sn 4+ were made into same volume for next experiments. The physical phases of the coatings were analyzed by SEM and XRD. Based on the electrochemical tests and accelerated life tests, we concluding that the precursor prepared through 1PS liquid-phase filtering paper was more homogeneous and had a longer service life. The optimum molar mass of the coating solute was 0.9 mol/L Sn 4+ which need 6 times of sintering, and the preparation efficiency was 43% higher than before. Meanwhile, the chlorine evolution potential was reduced by 22 mV and the service life was increased to nearly 2.6 times because of the better coating state and better bonding force with titanium substrate.